2012
DOI: 10.1093/carcin/bgs226
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplakin acts as a tumor suppressor by inhibition of the Wnt/β-catenin signaling pathway in human lung cancer

Abstract: Desmosomes are intercellular junctions that confer strong cell-cell adhesion, thus conferring resistance against mechanical stress on epithelial tissues. A body of evidence indicates that decreased expression of desmosomal proteins is associated with poor prognosis in various cancers. As a key component of desmosomal plaque proteins, the functional role of desmoplakin (DSP) in cancer is not yet elucidated. Here, we reported the anti-tumorigenic activity of DSP in non-small cell lung cancer (NSCLC). We found by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 41 publications
5
91
2
1
Order By: Relevance
“…The majority of those studies investigated JUP in conjunction with other adhesive junctional proteins and demonstrated that loss of JUP expression, which is an early event in tumorigenesis, in conjunction with the lack of expression of other cell-cell adhesion proteins, such as E-cadherin, α-catenin, β-catenin, DSG, or desmoplakin, resulted in increased tumor formation and size and was correlated with advanced tumor stage, poor patient survival and increased metastasis (29). Decreased expression/loss of desmoplakin and DSG as tumor suppressors was reportedly attributed to invasive tumorigenic potential (9,11). PRP-1 did not exert any effect on occluding/tight junction proteins, such as claudins (data not shown) and E-cadherin (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of those studies investigated JUP in conjunction with other adhesive junctional proteins and demonstrated that loss of JUP expression, which is an early event in tumorigenesis, in conjunction with the lack of expression of other cell-cell adhesion proteins, such as E-cadherin, α-catenin, β-catenin, DSG, or desmoplakin, resulted in increased tumor formation and size and was correlated with advanced tumor stage, poor patient survival and increased metastasis (29). Decreased expression/loss of desmoplakin and DSG as tumor suppressors was reportedly attributed to invasive tumorigenic potential (9,11). PRP-1 did not exert any effect on occluding/tight junction proteins, such as claudins (data not shown) and E-cadherin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The loss or reduction of one or more desmosome components, including DSG 1-3, DSC 2, DSC 3, JUP, PKP 1-3 and DSP, is observed during development and/or the progression of various human cancers. Adherens junctions and desmosomes are known to be downregulated in cancer, as they exert tumor-suppressive effects (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies of DSP in human lung disease indicate that gene expression is decreased in the majority of lung cancer cell lines (14). These cell lines demonstrated hypermethylation in the promoter and intron 1 regions of the gene, indicating that epigenetic mechanisms may regulate DSP gene expression.…”
mentioning
confidence: 87%
“…DSP has been shown to inhibit Wnt/␤-catenin signaling pathway through regulation of plakoglobin, ␤-catenin, and matrix metalloproteinase 14 in a lung cancer model (65). Aberrant activation of Wnt/␤-catenin signaling pathway has been implicated in the development of pulmonary fibrosis (6) and is, thus, one potential mechanism for a profibrotic role of DSP in IPF.…”
Section: Genetic Variants Affecting Epithelial Cell Integritymentioning
confidence: 99%